2017
DOI: 10.4103/0972-9941.181368
|View full text |Cite
|
Sign up to set email alerts
|

Is mini-laparoscopic cholecystectomy any better than the gold standard?: A comparative study

Abstract: BACKGROUND:Mini-laparoscopic cholecystectomy (MLC) has widened the horizons of modern laparoscopic surgery. Standard four port laparoscopic cholecystectomy (SLC), which has long been established as the “Gold Standard” for gall bladder diseases, is under reconsideration following the advent of further minimally-invasive procedures including MLC. Our study aims to provide a comparison between MLC and SLC and assesses whether MLC has any added benefits.MATERIALS AND METHODS:Patients with symptomatic gall bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Standard four-port laparoscopic cholecystectomy (LC) is considered to be a gold standard technique for cholecystectomy [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Standard four-port laparoscopic cholecystectomy (LC) is considered to be a gold standard technique for cholecystectomy [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is notable that in their study, an endocatch bag was used to deliver the GB out through the 5 mm port, which is different from the technique described in our paper. Shaikh et al compared the use of the standard four trocars (10 mm × 2, 5 mm × 2) with mini-laparoscopic cholecystectomy using three 3 mm ports and one 10 mm port, and found that the latter was not only comparable to the standard ports in terms of blood loss, post-operative pain, analgesia requirement and mobilisation, but was also associated with earlier return to work and superior cosmetic outcomes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have suggested that the mini-port technique has more cosmetic outcomes than the standard-port technique; however, they have a similar effect on pain, nausea, and vomiting after LC. 20 - 22 Results of single-incision LC are inconsistent. 23 - 25 Type of anesthesia also contributes to the occurrence of complications after LC.…”
Section: Discussionmentioning
confidence: 99%